Sebuah Catatan Kecil Pengembangan Modul dengan Metode ADDIE dalam Peningkatan Literasi Finansial Siswa di MAN Sidoarjo - Zain Fuadi Muhammad Roziqi Fath (Journal on Education, 2024)
An individual's financial literacy can be described if the individual takes action regarding the financial arrangements owned by the individual concerned. So it becomes quite an important thing for an individual to have. Financial literacy in Indonesia itself cannot be said to be good enough. This is because the National Survey of Financial Literacy and Inclusion conducted by the Financial Services Authority (OJK) found that the level of financial literacy and inclusion of Indonesian people had increased. Indonesia's Financial Literacy Index score in 2022 is 49.68%. This research is a quantitative descriptive research with data collection methods through questionnaires and observation. Based on the tests carried out in this research, the results obtained show that impulsive purchases and the tendency to choose online loans have positive values. This means that the higher the price for excessive consumption, the more someone will increase the amount of their debt in online loans.